Big Data Analytics in Business Research: Challenges and Opportunities - Rama Krishna Mani Kanta Yalla (AG Volumes, 2024)
Business research has become heavily influenced by big data analytics. This review paper examines the multidimensional character of big data from the perspective of the Six V’s: Through the examination of these dimensions, we acquire a thorough comprehension of the potential and characteristics of big data. Businesses are confronted with many challenges when employing big data analytics, despite its transformative potential. In contrast, the opportunities that big data analytics offers are substantial. The purpose of this paper is to offer an in-depth look of the opportunities and challenges associated with big data analytics in business research, as well as to provide insight into how organisations can effectively implement and leverage on these advancements.